The Kernel Pitman-Yor Process - Chatzis,SP; Korkinof,D; Demiris,Y (2012)
In this work, we propose the kernel Pitman-Yor process (KPYP) fornonparametric clustering of data with general spatial or temporalinterdependencies. The KPYP is constructed by first introducing an infinitesequence of random locations. Then, based on the stick-breaking construction ofthe Pitman-Yor process, we define a predictor-dependent random probabilitymeasure by considering that the discount hyperparameters of theBeta-distributed random weights (stick variables) of the process are notuniform among the weights, but controlled by a kernel function expressing theproximity between the location assigned to each weight and the givenpredictors.